Effect of liposomal drug based on interferon and extract from Silybum marianum on antioxidative status of bulls against the background of contamination of fodders by cadmium and plumbum - Gutyj, B. V.; Martyshuk, T. V.; Parchenko, V. V.; Kaplaushenko, A. H.; Bushueva, I. V.; Hariv, I. I.; Bilash, Y. P.; Brygadyrenko, V. V.; Turko, Y. I.; Radzykhovskyi, M. L.; Парченко, Володимир Володимирович; Каплаушенко, Андрій Григорович; et al. (My University, 2022)
The balance between anti- and prooxidants in animal organisms in general and in each cell in particular is responsible for the regulation of many metabolic processes that provide immunocompetence, growth, development and protection of animals from oxidative stress, related to inflow of cadmium and plumbum. Therefore, the objective of our study was the influence of a liposomal drug based on interferon and milk thistle (Silybum marianum (L.) Gaertn.) on the antioxidative status of the organism of bulls in the conditions of cadmium and plumbum loading. The experiments were performed on six-months-old Black Motley dairy cattle. The fodders in the farm were determined to contain high levels of plumbum and cadmium. The liposomal drug Lipointersyl inhibited the lipid peroxidation processes in the bulls. The drug components promoted the decrease in the level of intermediate and end products of lipid peroxidation, in particular 22% decrease in the level of diene conjugates and 20% decrease in TBA-active products. Intramuscular injection of the liposomal drug to bulls of the experimental group strengthened the antioxidant protection of their organism. On the 30th day of the experiment, blood from experimental group animals was seen to have a 9.8% increase in reduced glutathione. Assay of the enzymatic link of the glutathione system revealed that the activity of glutathione peroxidase and glutathione reductase in the blood of the animals that had been injected the liposomal drug Lipointensyl had increased by 24.0% and 27.7% respectively by the 30th day of the experiment. The experiments conducted on young cattle demonstrated that intermuscularly injected the Lipointensyl liposomal drug – against the background of cadmium and plumbum loading – promoted the activation of the glutathione system of antioxidant protection as a result of increase in the activity of its enzymatic and nonenzymatic links. The study of catalase and superoxide dismutase activities revealed that on the 30th and 40th days of the experiment, the activity of those enzymes varied within the physiological norms. Therefore, the analyzed Silybum marianum-based liposomal drug has antioxidant properties, it is recommended for young cattle in the conditions of contamination with heavy metals in order to prevent the development of oxidative stress.
Keywords: heavy metals; glutathione system; catalase; superoxide dismutase; diene conjugates; liposomes